Pokojninska reforma je sprejeta, naj živi reforma! - Božič, Tilen (Podjetje in delo, 2020)
The pension system is dynamic and self-generates a strong inertia, which must be constantly adapted to the "zeitgeist". Delays in the development of the system can have drastic consequences. These first appear in the form of major interventions (reforms) that seek to catch up by using shortcuts that inevitably trigger political tensions and a drop in public confidence. The strategy for the future development of the pension system should be a result of a broad public consensus in order not to lose its focus over time due to changes and pressures of daily politics. Instant confusions caused by shocks, such as changes of the government or the Covid 19 epidemic, bring a stalemate in the pace of the reform and often serve as hunting grounds to partial interests and initiatives that would be smoothly rejected in less hectic times. The awareness of the public, the media and the experts may serve as a lighthouse in troubling times, making sure that the policymaker does not get lost in the woods of partial interests.